In situ X-ray imaging of defect and molten pool dynamics in laser additive manufacturing - Leung, Chu Lun Alex; Marussi, Sebastian; Atwood, Robert C.; Towrie, Michael; Withers, Philip J.; Lee, Peter D. (Nature communications, 2018)
The laser–matter interaction and solidification phenomena associated with laser additive manufacturing (LAM) remain unclear, slowing its process development and optimisation. Here, through in situ and operando high-speed synchrotron X-ray imaging, we reveal the underlying physical phenomena during the deposition of the first and second layer melt tracks. We show that the laser-induced gas/vapour jet promotes the formation of melt tracks and denuded zones via spattering (at a velocity of 1 m s −1 ). We also uncover mechanisms of pore migration by Marangoni-driven flow (recirculating at a velocity of 0.4 m s −1 ), pore dissolution and dispersion by laser re-melting. We develop a mechanism map for predicting the evolution of melt features, changes in melt track morphology from a continuous hemi-cylindrical track to disconnected beads with decreasing linear energy density and improved molten pool wetting with increasing laser power. Our results clarify aspects of the physics behind LAM, which are critical for its development. Additive manufacturing of metals is now widely available, but the interaction of the metal powder with the laser remains unclear. Here, the authors use X-rays to image melt features and pore behaviour during laser melting of powders.